Interrogative Construction In Malay Batu Bara - Sitinjak, Dedy Rahmad; Mulyadi, Mulyadi (Universitas Negeri Semarang, 2024)
Question sentences are indicators that form introductive constructions, so for the formation of interrogative sentences, question sentences need special attention because question sentences are a way for a person to get complete information. This research is entitled Interrogation Construction in Batu Bara Malay (BMBB). This study seeks to analyze the Integrative construction. The research method used in this study is qualitative because it can be used to research the natural condition of the object; the instruments used in this study are sound recording devices, video recording tools, and stationery. The data used in this study is speech data in BMBB. The data for this research is sourced from the BMBB user community. After obtaining data in the field, the data is analyzed and described in words. The results of this study are that BMBB has an open interrogatory construction with nine interrogative words found, namely apo, siapo, kenapo, berapo, mano, dimano, darimano, kamano, and gimano, a closed-in cogitative construction with interrogative words found in 2 rows, namely Apo and Gekmano, For rhetorical interrogatory constructs with interrogative words found in 3 rows, namely siapo, mangapo, and gekmano.